Peningkatan Keberdayaan Wanita Penghasil Produk Kopi Melalui Kelembagaan Kwt Mekar Sari di Desa Tulungrejo Ngantang Malang Jawa Timur - Rokhani; Sofia; M.Rondhi; Novikarumsari, Nurul Dwi (Universitas Mataram, 2023)
The Mekar Sari Women Farmers Group (KWT) was formed in 2018 with 15 members, with a productive economic business processing Robusta coffee into ground coffee, because coffee is one of the products produced by farmers in Tulungrejo Village, Ngantang District, Malang Regency. However, this KWT institution still needs strengthening with indications that only a few members are active. In addition, processed coffee products have not been managed seriously, production is only limited to meeting local level customer demands. Seeing this condition, the lecturers' scheme of service in the village of origin is concerned with strengthening KWT institutions and processed coffee products, especially in terms of packaging and marketing, by utilizing digital platforms (social media). Institutional strengthening of KWT is important as an effort to sustain the KWT business, especially from an economic standpoint to increase the income of women in Tulungrejo Village. The sustainability of this business is strongly supported by strong social capital, meaning that there is a close relationship between social capital and business continuity (Handayani, 2007). This institutional strengthening is carried out with lectures, informal discussions by inviting speakers from KWT who are more advanced as a source of inspiration for KWT Mekar Sari. Meanwhile, interventions from the marketing side were carried out to expand the market for Robusta coffee products by utilizing social media networks. Intervention in the form of packaging is carried out as an attraction for consumers, considering that so far packaging is still very simple